Program Belajar berbasis STEM untuk Pembelajaran IPA: Tinjauan Pustaka, dengan Referensi di Indonesia - Nugroho, Oktian Fajar; Permanasari, Anna; Firman, Harry (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
The scenario of Industry 4.0 and 21st century skills show rapidly increase and informed. In this century, the main goal of our educational system should be able to answer students needed for living in the world. In recent years, STEM Education has received growing attention to be considered to understand STEM Education. In the South East Asia, Indonesia is one of the biggest country has a large number of human resources that should be developed. This study was aimed to examine the movement of STEM education in Indonesia within the scope of 21st century skills categories by using the content analysis method, examine best practice of STEM education for teachers by investigating engineering design skills training and reviewed the literature from 1990 to 2016 that has emphasized on development of STEM education around the world. The findings showed that STEM Education has been developed around Indonesia and has a positive impact to enhance students? concept comprehension, literacy, and creativity. Many researches provide evidence the best practice for science teacher to implement STEM Education. STEM has a close to daily life and increase student awareness with the environment.